Confocal Imaging of Cells in Thick Rat Cerebrum Using Hoechst Stain - Sharma, Aparna; Natanasabapathi, Gopishankar; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
Confocal microscopy is an imaging technique that offers a high-resolution imaging capability for structures at the cellular level, hence making it valuable for examining thick brain tissues such as rat cerebrum. This research aimed to evaluate the possibility of using confocal microscopy with Hoechst 33342 staining to determine the nuclear architecture in a thick section of the cerebrum. Due to the high resolution, light penetration in thick parts of the brain tissues is relatively challenging. Combined with Hoechst staining, confocal microscopy facilitates visualization and observation of nuclear characteristics to reflect on neurogenesis, the development of the brain, and its pathologies.Male Wistar rats were taken for the experiment after institutional ethical permission, and their brains were sectioned into small sections of 2-mm slices in a Petri dish containing Dulbecco's phosphate buffered saline to maintain the viability. Hoechst 33342 staining was used to detect the nuclei, and samples within the live media were imaged using a confocal laser scanning microscope. A z-stack imaging approach was employed to reconstruct three-dimensional representations of nuclear organization.Nuclei in thick sections of the cerebrum could be visualized by confocal microscopy, using Hoechst staining to achieve strong fluorescence signals. Three-dimensional reconstruction shows that nuclei were homogeneously distributed throughout the tissue, while having a higher density in the cortex.This study demonstrates that confocal microscopy combined with Hoechst staining is useful in three-dimensional imaging of the thick brain tissues. Although some challenges, including signal attenuation, are encountered in this approach, it provides sufficient details on the nuclear architecture. Future integration of advanced techniques like tissue clearing and adaptive optics might enhance the depth and resolution, thereby broadening its applications to neuroanatomical and pathological studies.
Keywords: cerebrum; confocal Imaging; Hoechst stain; z-stack